Gastric cancer with brain metastasis: from molecular characteristics and treatment - Zhu, Yingze; Zhou, Miao; Li, Congling; Kong, Wenyue; Hu, Yuning (Frontiers in Oncology, 2024)
Gastric cancer is one of the cancers with increasing incidence and ranks fourth globally among the most frequent causes of cancer-related mortality. Early gastric cancer is often asymptomatic or presents with atypical symptoms, and the majority of patients present with advanced disease upon diagnosis. Brain metastases are present in approximately 1% of gastric cancer patients at the time of diagnosis, which significantly contributed to the overall mortality of the disease worldwide. Conventional therapies for patients with brain metastases remain limited and the median overall survival of patients is only 8 months in advanced cases. Recent studies have improved our understanding of the molecular mechanisms underlying gastric cancer brain metastases, and immunotherapy has become an important treatment option in combination with radiotherapy, chemotherapy, targeted therapy and surgery. This review aims to provide insight into the cellular processes involved in gastric cancer brain metastases, discuss diagnostic approaches, evaluate the integration of immune checkpoint inhibitors into treatment and prognosis, and explore the predictive value of biomarkers in immunotherapy.